MODERATE ISLAM REVISITS: A Lesson from T.M. Hasbi Ash-Shiddieqy’s Interpretation of Wasathiyah in Tafsir An-Nuur - Razali Ibrahim, Muhammad Syahrial (Journal of Contemporary Islam and Muslim Societies, 2022)
Abstract: The specific objective of this this article is to explore Muhammad Hasbi As-Shiddieqy's conceptualization of the term wasathiyah, which is analitically studied from his work “Tafsir An-Nuur.” His conceptualisation is of interest because previously published studies on moderate Islam are not consistent, while Hasbi’s contribution offers some important insights intoresolving this discrepency. In additions, Hasbi’s signification of the termof wasathiyah is found elsewhere in in many of his fiqh books, which is used as secondary sources. By using descriptive interpretive analysis, it is found that wasathiyah, in Hasbi's view, is an attitude of life that can bring humans true happiness by referring to the Quran. Then, happiness itself is understood as the ability to solve various problems based on the concept of ijtihad. He emphasized that the essence of wasathiyah is an attitude of life that can make Islamic society advanced and civilized by promoting moral values, such as justice, tolerance, openness, and respect for diversity.Therefore, I argue that Hasbi’s conceptualisation of the term might bring harmony between the group who are for traditionalism and against modernism, and the other who advocate liberalism and modernism.Keywords: moderate Islam, wasathiyah, Muhammad Hasbi Ash-Shiddieqy, Tafsir An-Nuur